Genetic algorithm in the allocation of hours of an institute of higher education [Algoritmo genético en la asignación de horarios de un instituto de educación superior] - Salvador León, Nilo (2020)
ABSTRACT Administrative management in technological higher education institutions is of utmost importance to achieve their strategic objectives, one of the most important processes is the generation of class schedules, in this process the complexity varies according to the number of classes that are taught , the semesters of each degree that is opened and the number of classrooms available. The present research work was carried out with the aim of determining the influence of the genetic algorithm in improving the allocation of schedules at the John A. Mackay Higher Education Institution during the year 2019. The type of study was pre-experimental; with a sample of 2 technical professional careers of the institution and considering 3 factors within the process, which were time, cost and results. The genetic algorithm was implemented with the SCRUM software development methodology, its main advantage being to develop systems in a short period of time and great flexibility to changes during development. The preexperimental research resulted in an 84.42% reduction in the time spent, for costs it decreased by 84.71%, and finally the use of the classrooms was optimized by 5%; achieving a more efficient allocation of schedules.